Enhancing Biology Students’ Mastery of Animal Anatomy with a Web-Based Electronic Atlas: Toward Sustainable Digital Learning Tools - Sulistiyawati Sulistiyawati; Farida Hanum; Tien Aminatun; Cecilia Yanuarief (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Learning animal anatomy in higher education often suffers from limitations in terms of visual media and practical time. Technology-based solutions such as web-based electronic atlases (e-atlases) can improve conceptual understanding and support digital continuous learning. This study aims to evaluate the effectiveness of web-based e-atlas in improving biology students' animal anatomy learning outcomes through a flipped classroom approach. This study used the ADDIE development model and a quasi-experimental design with a pretest-posttest control group approach. A total of 130 third semester students from three universities in Yogyakarta were divided into control (n=64) and experimental (n=66) classes. Instruments in the form of objective tests were validated by experts, and data were tested using Gain Score, N-gain, and t-test with parametric assumptions. The experimental class using e-atlas showed a significant increase in learning outcomes (N-gain=0.75; high category) compared to the control class (N-gain=0.29; low category), with significant differences based on t-test (p<0.001). These results support that e-atlas integration is effective in improving students' anatomical literacy. The use of web-based e-atlas in flipped classroom learning is effective, efficient, and has the potential to support the sustainability of biology learning. The findings recommend continued development of digital media to expand access and reduce reliance on physical animal dissection.